Prevent and preempt obesity, promote and protect health - Fatema Jawad; Sanjay Kalra (Journal of the Pakistan Medical Association, 2025)
Obesity has emerged as a major public health challenge,not only in Pakistan and its neighbouring countries, butacross the world.1 Along with its myriad clinicalpresentations, complications and comorbidities, thevarious causative, contributory and confounding featuresof obesity serve to confuse an already complex situation.While the diagnosis of obesity should be straightforward,this is not always the case. Various countries have their owndiagnostic thresholds for body mass index and waistcircumference. These are decided according to the risk ofcardiovascular disease. Asians, in general, have highercardiovascular morbidity at a relatively lower body weight.The intricacies of obesity diagnosis and classification havealso been increased, rather than eased, by the emergenceof newer terms such as preclinical obesity, metabolicallyhealthy obesity, and clinical obesity.2 The present figures of obesity in the adult population ofthe Indo-Pak population are of concern. India has a muchlarger population with the NFHS-5 (2019-2021) datashowing 38% women and 36% men between the ages of 15 to 49 years being obese.3 The second NDSP (2016-2017)study from Pakistan revealed figures of obesity being 42%in males and 58% in females.4 Continued....